Review of the Movie "21 Rubies" - ANTON, Andreas (Studia Universitatis Babeș-Bolyai Historia, 2025)
The movie 21 Rubies represents, as a cinematic genre, a drama released on November 3, 2023, directed by the Romanian priest and filmmaker Ciprian Mega. I chose to write this review because watching this film made me reflesct on my relatively recent past, specifically my high school years. There are many films that evoke various emotions in people's hearts, with some of the most well-known being Titanic and Gladiator and what 21 Rubies has in common with these two cinematic masterpieces is that it draws inspiration from reality, even though there is an apparent intent to maintain silence regarding the functioning of the Romanian Orthodox Church (ROC) as an institution. The subject of the film is relevant because it aims to highlight the situation within the hierarchy and educational system of the Romanian Orthodox Church, on one hand, and the political games at the top levels of the state, on the other hand, and how all these lead to the inefficiency of justice and the failure of the rule of law. The two-and-a-half-hour film unfolds on two timelines: one set chronologically at the end of 2022, and the other during the governance of the Romanian Democratic Convention (1996-2000). Although the two developments of the action seem initially entirely distinct, they intersect notably in a symbolic moment when one of the film characters hands to Nina, the film main prosecutor a watch with 21 rubies, this act triggers a wave of sorrowful memories for her, recalling the tragic events that happened during the Convention's governance, where her parents and brother were among the victims.